Ethnicity and nation-building in Sri Lanka - Nayak, Subhash Chandra (Delhi : Kalinga Publications, 2001)
Study relates to the political institutions and their role in nation-building in Sri Lanka.
Keywords: Tamil (Indic people) -- Sri Lanka -- Politics and government; Sri Lanka -- Politics and government -- 1978-; Sri Lanka -- Ethnic relations -- Political aspects